2010
DOI: 10.1016/j.neuron.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Signaling Confers Ventral Telencephalic Progenitors with Distinct Cortical Interneuron Fates

Abstract: Summary Interneurons in the cerebral cortex regulate cortical functions through the actions of distinct subgroups that express parvalbumin, somatostatin or calretinin. The genesis of the first two subgroups requires the expression of NKX2.1, which is maintained by SHH signaling during neurogenesis. In this paper, we report that mosaic elimination in the medial ganglionic eminence (MGE) of Smo, a key effector of SHH signaling, reveals that MGE progenitors retain a remarkable degree of plasticity during the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
222
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(242 citation statements)
references
References 60 publications
18
222
2
Order By: Relevance
“…4G). As our previous studies have demonstrated that the higher levels of Shh signaling induce Nkx6.2 in the dorsal MGE relative to ventral MGE (Xu et al, 2005(Xu et al, , 2010a, and, as the relative levels of Nkx2.1 and Nkx6.2 transcript are similar in high versus low Shh-exposed cultures as they are in dorsal versus ventral MGE cells (Fig. 4I,J), Nkx2.1::mCherry + cells in our high and low Shh protocols have features of dorsal versus ventral MGE, respectively.…”
Section: Efficient Telencephalic Patterning In Mescsmentioning
confidence: 81%
See 2 more Smart Citations
“…4G). As our previous studies have demonstrated that the higher levels of Shh signaling induce Nkx6.2 in the dorsal MGE relative to ventral MGE (Xu et al, 2005(Xu et al, , 2010a, and, as the relative levels of Nkx2.1 and Nkx6.2 transcript are similar in high versus low Shh-exposed cultures as they are in dorsal versus ventral MGE cells (Fig. 4I,J), Nkx2.1::mCherry + cells in our high and low Shh protocols have features of dorsal versus ventral MGE, respectively.…”
Section: Efficient Telencephalic Patterning In Mescsmentioning
confidence: 81%
“…First, whereas, within a given cortical layer, PVand SST-expressing interneurons have similar birthdates (Cavanagh and Parnavelas, 1988;Rymar and Sadikot, 2007), the predominance of PV over SST subgroups in the later-born, superficial cortical layers corresponds to a larger percentage of all SST interneurons being generated earlier than all PV interneurons (Butt et al, 2005;Xu et al, 2010b). Second, higher levels of signaling for the morphogen Shh in dorsal MGE appears to bias those Nkx2.1-expressing progenitors to generate SST-expressing interneurons (Xu et al, 2005(Xu et al, , 2010aWonders et al, 2008) (schematized in Fig. 4A).…”
Section: Efficient Telencephalic Patterning In Mescsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shh signalling is required for specifying MGE identity and for the formation of somatostatin and parvalbulim interneurons, and loss of Shh signalling leads to increased calretinin interneuron development in vivo 43 . However, although the CGE develops independently of Shh 44 , during ESC differentiation the inhibition of Shh generates glutamatergic neurons and never gives rise to Gsx2 progenitors or calretinin interneurons 14,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inhibition of Shh signaling suppresses the self-renewal capacity of pancreatic cancer stem cells and reverses chemotherapy resistance (16). Shh may also downregulate GSH2 in ventral telencephalic progenitors (17), suggesting that Shh signaling is able to suppress GSH2 under certain conditions.…”
Section: Discussionmentioning
confidence: 99%